1996
DOI: 10.1063/1.115754
|View full text |Cite
|
Sign up to set email alerts
|

Structure of cross-tie wall in thin Co films resolved by magnetic force microscopy

Abstract: We have studied the magnetic domain structure of a thin polycrystalline Co film by magnetic force microscopy (MFM). Domain walls of the cross-tie type have been observed for a Co film of 50 nm thickness. Due to the high lateral resolution of MFM we have been able to study the magnetic structure of a single cross tie. We have determined locations of Bloch lines within a domain wall comparing the experimental data with a theoretical model of a cross-tie wall. In order to explain our experimental results we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 0 publications
2
34
0
3
Order By: Relevance
“…As the ferromagnet thickness decreases, demagnetizing fields increase, which means that it becomes increasingly energetically favorable for domain walls to mutate from the out-of-plane to in-plane direction. This has been demonstrated in experiments in Co, Permalloy (Py), and Ni samples, [19][20][21][22] where it has been observed that the transition between these two types of domain walls occurs at around 30 nm for Co and 20 nm for Ni.…”
Section: Introductionmentioning
confidence: 80%
“…As the ferromagnet thickness decreases, demagnetizing fields increase, which means that it becomes increasingly energetically favorable for domain walls to mutate from the out-of-plane to in-plane direction. This has been demonstrated in experiments in Co, Permalloy (Py), and Ni samples, [19][20][21][22] where it has been observed that the transition between these two types of domain walls occurs at around 30 nm for Co and 20 nm for Ni.…”
Section: Introductionmentioning
confidence: 80%
“…Many of the results on the theory of the domain walls can be found in books [1,2]. In particular, there are analytical expressions for the distribution of the magnetization vector inside of the one-dimensional Bloch and Néel domain walls, which are the starting point for calculating their static and dynamic properties.The cross-tie domain wall was also observed in a number of experiments a that time (see Ref.3 and references therein) and also with modern high resolution techniques [4,5,6], and are usual in thin and ultra-thin magnetic films important for modern applications [7]. However, there is no [4] (also see p. 163 in Ref.…”
mentioning
confidence: 99%
“…3 and references therein) and also with modern high resolution techniques [4,5,6], and are usual in thin and ultra-thin magnetic films important for modern applications [7]. However, there is no [4] (also see p. 163 in Ref.…”
mentioning
confidence: 99%
“…7a (running from its top to bottom) is characterized by the presence of four segments: dark and bright ones on each side of the domain wall (with reversed contrast with respect to the wall, see encircled areas in the image). Such a MFM image is typical for cross-tie wall [42]. In regions such as that shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…5a-f). The ripple structure is directly related to the polycrystalline character of the studied films and is due to local variations of the magnetic anisotropy [39,42]. The ripple direction is always oriented perpendicular to the magnetization direction and hence the magnetic easy axis [39,42].…”
Section: Resultsmentioning
confidence: 99%